Peran Wanita sebagai Ibu Keluarga dan perannya di Ranah Publik: Studi kasus di Desa Ngliman Kecamatan Sawahan Kabupaten Nganjuk - Nandipah Roazah (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2024)
The observation conducted in Ngliman Village, Sawahan District, Nganjuk Regency aims to determine the responsibilities of women as mothers and in society. The methods used in this observation are case studies and qualitative methodology. Data collection was carried out using three methods, namely: 1) observation, 2) interviews, and 3) documentation. The data analysis methods used are 1) data reduction, 2) data presentation (data presentation), and 3) drawing conclusions/verification. In Ngliman Village, Sawahan District, Nganjuk Regency, the results of the observation show that women act as mothers and caregivers of husbands in the fields. In Ngliman Village, Sawahan District, Nganjuk Regency, women still follow customs and culture about what to do after marriage. These customs include being a pure mother, helping her husband in the fields, having limited thinking development, and taking the initiative to sell at tourist attractions if they marry young. The position of women in the public space of the Ngliman community, Sawahan District, Nganjuk Regency: women are encouraged to engage in social activities such as sharing, cleaning, and vegetable gardening, which can help the community grow financially and progress.